ARTIFICIAL INTELLIGENCE AS SUBJECT OR INSTRUMENT: PHILOSOPHICAL AND LEGAL BOUNDARIES OF RESPONSIBILITY - Sitora F. Abdusattarova (Bright Mind Publishing, 2026)
The article presents a philosophical and legal analysis of the problem of the legal subjectivity of artificial intelligence in the context of the digital transformation of society. The increasing autonomy of algorithmic systems and their active integration into public administration, judicial practice, and economic governance raise the question of whether artificial intelligence may be recognized as an independent subject of law. The study draws a distinction between the ontological and normative status of artificial intelligence, thereby avoiding the conflation of technological autonomy with moral subjectivity.
Keywords: Artificial intelligence; legal subjectivity; legal responsibility; algorithmic governance; digital transformation; philosophy of law; autonomy; electronic personhood.